PENGARUH KEPEMIMPINAN ADAPTIF TERHADAP KESIAPAN TRANSFORMASI DIGITAL DI PERUSAHAAN TEKNOLOGI - Candra Surya; Giatman Giatman; Ambiyar Ambiyar; Hasan Maksum; Remon Lapisa; Fadhilah Fadhilah (Universitas Muhammadiyah Ponorogo, 2025)
Digital technology development requires companies to transform in order to compete in the era of the Industrial Revolution 4.0. This research aims to analyze the influence of adaptive leadership on digital transformation readiness in technology companies. Adaptive leadership encompasses the ability to manage change, solve complex problems, empower teams, communicate flexibly, and manage uncertainty. Digital transformation readiness includes aspects of technology, organization, human resources, strategy, and digital culture. This research used a quantitative approach with the simple linear regression method. The results of the t-test show a significance value of 0.029 (< 0.05) and a regression coefficient of 0.246, which means that adaptive leadership has a positive and significant influence on digital transformation readiness. The higher the level of adaptive leadership in the organization, the more prepared the company is to face technology-based changes. These findings affirm the important role of adaptive leaders in creating an innovative, collaborative, and flexible work environment to support the success of digital transformation. This research is expected to serve as a reference for organizations in developing a leadership model that aligns with the dynamics of contemporary technological change.